Second malignant neoplasms in children and adolescents in Moscow Region - D. Yu. Kachanov; R. T. Abdullaev; N. V. Kruchko; T. V. Shamanskaya; E. V. Inyushkina; K. V. Dobrenkov; S. R. Varfolomeeva (Онкогематология)
Second malignant neoplasms are the most devastating consequences of anticancer therapy. We have studied the frequency of second malignant neoplasms among children and adolescents in Moscow Region. 10 cases were observed during the years 2000—2008. Longterm survival can be archived in some patients using multimodal treatment.